Introduction to the study of the circulation of Mémoires Garibaldi (1860) (TEL Tempo, Espaço e Linguagem, 2022)
This article presents a possibility of study that strengthens the debate on the relationship between History and Literature. It stems from our doctoral research dedicated to the study of the transatlantic circulation of the Mémoires de Garibaldi, published in 1860 by Alexandre Dumas in Paris. In this sense, we seek to reflect on the methodology brought by scholars on the subject, led in Brazil by Márcia Abreu.Key-words: History. Literature. Memoirs. Garibaldi. Dumas